Partisipasi Masyarakat Dalam Pembiayaan Pendidikan Di Sd Ta'mirul Islam Surakarta - Supoyo, Supoyo (2016)
The research is aimed to describe: 1) the process of community's participation mobilization in educational financing; 2) the educational financing accuntability; and 3) the suppporting and inhibiting factors in community's participation mobilization in educational financing at SD Ta'mirul Islam of Surakarta. The type of the research is qualitative research with the ethnographic design. The object of the research is community's participation mobilization in educational financing at SD Ta'mirul Islam of Surakarta. The data collecting technique were done using in-depth interview, observation and document. The data analysis technique was done using interactive model, that consist of data reduction, data display, and verification. Based on the analysis, the research concludes that: 1) the process of community's participation mobilization in educational financing at SD Ta'mirul Islam of Surakarta was initiated since the enrollment of new students. It was done through the announcement of the requirements and educational financing for new students. The community's participation in educational financing at SD Ta'mirul Islam of Surakarta comprise of four types, namely: a) Dana Pengembangan Pendidikan; b) SPP; c) Infaq; and d) Other forms; 2) the educational financing management accountability at SD Ta'mirul Islam of Surakarta is done through the budget transparency that is done since the planning thrughout the reporting process. The budget planning is done through the meeting in which the unit leaders proposed the budget. The meeting results, then, were proposed to the foundation to get approval. Having being approved, the budget plan, being provided to the parents; and 3) the supporting factor of community's participation mobilization in educational financing at SD Ta'mirul Islam of Surakarta cover the highly support of parents, and related institutions. The only inhibiting factor of community's participation mobilization in educational financing at SD Ta'mirul Islam of Surakarta was the parental economic condition.